CURRENT STATUS OF NURSING CARE FOR PATIENTS UNDERGOING TRANSORAL ENDOSCOPIC THYROIDECTOMY AT THAI NGUYEN CENTER FOR ONCOLOGY (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the current status of preoperative and postoperative care for patients undergoing transoral endoscopic thyroidectomy (TOETVA) at Thai Nguyen Center for  Oncology. Subjects and Methods: A descriptive study was conducted on 47 patients who underwent transoral endoscopic surgery for thyroid tumors (benign or malignant) from January 2024 to June 2025 at Thai Nguyen Center for Oncology. Results: All patients (47/47) preoperatively received instructions on fasting and oral hygiene and strictly followed the protocol. Nearly two-thirds of patients experienced moderate pain on the second postoperative day (28/47). 100% of patients were instructed on postoperative oral care, chin bandaging, and supportive care procedures; all patients complied with medical orders. Additionally, 91.2% received nutritional counseling, 100% were advised on follow-up compliance, and 100% were guided on neck exercises. Most patients adhered to postoperative instructions: 87.2% for oral hygiene, 80.9% for chin bandaging, and 91.5% for neck exercises. Conclusion: The results indicate that preoperative and postoperative care, including patient education, were thoroughly implemented. However, some limitations in patient compliance regarding postoperative care remain.
Keywords: Postoperative care, Transoral endoscopic thyroidectomy, Thyroid tumor, Preoperative instructions.